Adjuvant pegylated liposomal doxorubicin versus epirubicin sequential paclitaxel in triple-negative breast cancer: comparable efficacy with a distinct safety profile - Cai, Shuanglong; Yu, Shaohong; Lin, Xiuquan; Zhou, Quan; Zheng, Xiaoxin; Chen, Hongdan; Ma, Tao; Chen, Xiaogeng; Sun, Hong; Shi, Yong (Frontiers in Immunology, 2026)
ObjectivePegylated liposomal doxorubicin (PLD), an improved formulation of doxorubicin, offers potential advantages in targeting and reduced systemic toxicity compared to conventional anthracyclines like epirubicin. This study aimed to compare the efficacy and safety of PLD followed by paclitaxel versus epirubicin followed by paclitaxel as postoperative adjuvant therapy for triple-negative breast cancer (TNBC).MethodsA total of 1,036 patients with TNBC who received postoperative adjuvant chemotherapy with either PLD sequential paclitaxel or epirubicin sequential paclitaxel were enrolled. The primary endpoint was disease-free survival (DFS). Adverse events were systematically documented. Multivariate Cox regression identified prognostic factors, and a predictive nomogram was developed.ResultsAt median follow-up, 1-, 3-, and 5-year DFS rates were 93.39%, 84.04%, and 84.04% for the PLD group versus 93.58%, 82.38%, and 81.73% for the epirubicin group (log-rank p = 0.58). Postoperative N stage, stromal tumor-infiltrating lymphocyte (sTIL) expression, and Ki67 expression were independent predictors of DFS. The prognostic model achieved C-indices of 0.874 (training set) and 0.853 (validation set). The PLD regimen was associated with a significantly lower incidence of most adverse events; however, nausea, mucositis, and hand-foot syndrome were more frequent in the PLD group.ConclusionIn adjuvant therapy for TNBC, PLD sequential paclitaxel demonstrated comparable efficacy to epirubicin sequential paclitaxel. However, PLD exhibited a distinct and generally more favorable safety profile, except for specific toxicities such as hand-foot syndrome and mucositis. The developed nomogram may aid in individualized prognosis prediction.